Soft robotic grippers: a review - Zhang, Youyou; Man, Jianhao; Liu, Xiaoang; Li, Shuai; Cao, Bo; Yu, Liang; Tan, Xiaojun (Frontiers in Materials, 2025)
Soft grippers, with their high flexibility and environmental adaptability, have shown promising applications in industrial automation, medical assistance, and underwater operations. This study provides a detailed analysis of various actuation methods, such as fluid pressure, mechanical force, electric fields, magnetic fields, and thermal fields, discussing their principles, applications, and limitations. Additionally, the applications of materials such as hydrogels, elastic polymers, shape memory alloys, shape memory polymers, magnetic materials, and liquid metals in soft grippers are summarized, highlighting their respective advantages and disadvantages. On this basis, a comprehensive analysis and outlook on the performance of soft grippers, the challenges they currently face, and their future development directions have been conducted. This article aims to provide comprehensive theoretical insights for the design and application of soft grippers, thus advancing the field.